2012
DOI: 10.1149/1.4718391
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ni and Co Deposition into Porous Silicon and the Influence of the Electrochemical Parameters on the Physical Properties

Abstract: Metal-nanostructures are electrochemically deposited within the pores of porous silicon to achieve a hybrid material with specific magnetic properties. For this purpose first the porous silicon template is prepared by wet etching of an n+-type silicon wafer offering pore-diameters between 30 and 100 nm, depending on the anodization parameters. Secondly a ferromagnetic metal is electrodeposited into the pores, whereas the metal structures can be precipitated with various geometries and different spatial distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Porous silicon filled with Ni nanostructures offers a coercivity of H C =300 Oe and a reduced remanence of M R /M S = 0.28 [9]. Co deposited within porous silicon leads to coercivities of about H C = 450 Oe and a reduced remanence of M R /M S = 0.13 [10]. So both materials have been combined to enhance the magnetic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Porous silicon filled with Ni nanostructures offers a coercivity of H C =300 Oe and a reduced remanence of M R /M S = 0.28 [9]. Co deposited within porous silicon leads to coercivities of about H C = 450 Oe and a reduced remanence of M R /M S = 0.13 [10]. So both materials have been combined to enhance the magnetic properties.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, the biocompatibility and nontoxicity of PSi/Co were also assessed. Rumpf et al [11] studied the effect of current density on the structural and magnetic properties of cobalt deposited PSi obtained by electrodeposition. In a more recent work, Bouzourâa et al [6] reported the effects of annealing temperature and immersion duration on PL characteristics of cobalt-porous silicon nanocomposites prepared via immersion method.…”
Section: Introductionmentioning
confidence: 99%
“…PSi/Co nanostructures can be produced by a variety of techniques such as immersion method, stain etching, and electrodeposition [6,8,11]. Among these techniques, electrodeposition provides the ability to tailor size, shape, and morphology of the Co deposited under a set of well controlled synthesis parameters [12].…”
Section: Introductionmentioning
confidence: 99%